Hymenoptera parasitoides associados às larvas de Lepidoptera em reflorestamento e sistemas agroflorestais da fazenda Canchim (Embrapa Pecuária Sudeste), São Carlos, São Paulo, Brasil - Pereira, Aline Garcia (2013)
Studies on flora and wildlife are important to help to understand the ecological processes that occur in response to use of management strategies. Hymenoptera are a key group for setting priorities for conservation, since they represent a high proportion of diversity of insects , being easily sampled. The aim of this study was to characterize the fauna of Hymenoptera parasitoids associated with Lepidoptera larvae in agrosilvopastoral and silviagricultural systems and in reforestation area (ecological corridor) of the Fazenda Canchim (Embrapa Pecuária Sudeste), São Carlos, SP, Brazil. Lepidoptera larvae collected with beating tray were kept in the laboratory until the emergence of adults or of their parasitoids. From hosts collected in the reforestation emerged 69 parasitoids, thus identified: Chalcididae, Chalcidinae (Conura); Ichneumonidae, Pimplinae (Neotheronia) and Campopleginae (Charops and Microcharops); and Braconidae, Microgastrinae (Apanteles, Diolcogaster, Distatrix, Glyptapanteles and Protapanteles). From those collected in the agrosilvopastoral and silviagriculture systems 267 hymenopteran parasitoids emerged thus identified: Braconidae, Agathidinae (Alabagrus), Braconinae (Bracon), Microgastrinae (Cotesia, Diolcogaster, Glyptapanteles, Pholetesor and Protapanteles), and Orgilinae (Orgilus); Ichneumonidae, Campopleginae (Casinaria, Charops and Microcharops); Chalcididae, Chalcidinae (Brachymeria and Conura); and Eulophidae, Entedoninae (Horismenus) and Eulophinae (Elachertus and Euplectrus). The environments studied are home to wide variety of genera of Hymenoptera parasitoids through greater availability of food resources for them and for their hosts (immatures and adults). Reforestation practices and use of mixed systems environment should be encouraged.